THE EFFECT OF TRAINING, WORKLOAD AND DISCIPLINE ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE OF EMPLOYEES OF THE GOVERNMENT EDUCATION SERVICE OF THE RIAU ISLANDS PROVINCE - Brian Kawasi; Ngaliman; Muammar Khaddafi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Examine how training, workload, and discipline impact employee performance through work satisfaction. A total of 52 respondents were used as samples. The study utilized a questionnaire with Likert scale to collect data for research purposes. Validity and reliability tests are conducted on the instrument, with normality and linearity tests being used to check assumptions. Analyzing data through the use of analysis techniques to understand how training impacts employee performance through work satisfaction at the Provincial Education Office Kepri. Findings from the research suggest that (1) training directly impacts employee performance with no significant influence, (2) workload directly impacts employee performance with no significant effect, (3) discipline has a direct and significant influence on employee performance, (4) training has a significant impact on employee performance through work satisfaction, (5) workload has a significant influence on employee performance through work satisfaction, (6) discipline plays a significant role in employee performance through work satisfaction.